(untitled) (Research, Society and Development, 2022)
Periocular hyperpigmentation is a skin change, which through excess melanin causes spots, being that there are several extrinsic and intrinsic triggering factors, the peeling procedure consists of the application of chemical agents. The aim of this study is to carry out a systematic review of the literature in order to analyze chemical peeling as a treatment for periorbital hyperpigmentation. A systematic literature review was carried out on the subject through scientific academic journals and articles, from 2002 to 2022. Editorials and opinions were excluded, was used as descriptors the Periorbital Hyperpigmentation, dark circles, pathophysiology, treatment with chemical peels, biochemical profile, biological mechanisms, idiopathic cutaneous hyperchromia of the orbital region, etiology, orbital hyperpigmentation, periorbital hyperpigmentation and treatments. Glycolic acid peeling has shown promise in the treatment of dark circles, but as the one with the highest incidence of side effects in the form of erythema and itching at 20% and ferulic acid peeling has emerged as a safe and effective modality for the treatment of HPO. The 10% thioglycolic acid gel peeling, in some studies, demonstrated the reduction of infraorbicularis hyperchromia, in addition to improving the cosmetic aspect of the region, with reduction of fine lines and skin atrophy. However, more research and clinical studies are needed, using chemical peels in the treatment of dark circles.